Voices in Silence: Intersectionality of Caste and Class in Arundhati Roy’s The God of Small Things - Dr. Shamshad Rasool; Anzala Noor; Aneesa Kalsoom (Dialogue Social Science Review (DSSR), 2025)
Caste is a rigid and deeply entrenched system of social stratification in South Asia. The identity assigned at birth has a profound influence on individual autonomy and societal interactions. This study examines the intersection of caste and class oppression in Roy’s novel The God of Small Things, with a particular focus on how the intersectional identities formed by caste, class, and social expectations contribute to the marginalization and ostracism of the characters from the lower strata. Employing Crenshaw's theory of intersectionality and the qualitative content analysis method, the study investigates the deeply ingrained social structures that affect the lived experiences of the characters. The findings reveal that the entrenched social hierarchies entrap lower-caste individuals, such as Velutha, and curtail their freedom while perpetuating systemic discrimination. Characters who dare transgress caste and class boundaries face harsh repercussions, including societal exclusion, condemnation, violence, and enforced silence. The analysis also demonstrates that female characters suffer dual oppression through patriarchal control and moral surveillance. Additionally, the study examines the fragmentation of characters’ identity and the intergenerational transmission of trauma and fear. Roy’s narrative thus represents a strong critique of the ways caste and class shape not only the characters’ public life but also infiltrate their intimate domains of personal experiences. Key Words: Caste, social discrimination, stratification, oppression, untouchability, identity fragmentation, social exclusion.